2010
DOI: 10.1002/lt.22085
|View full text |Cite
|
Sign up to set email alerts
|

The biopsied donor liver: Incorporating macrosteatosis into high-risk donor assessment

Abstract: To expand the donor liver pool, ways are sought to better define the limits of marginally transplantable organs. The Donor Risk Index (DRI) lists 7 donor characteristics, together with cold ischemia time and location of the donor, as risk factors for graft failure. We hypothesized that donor hepatic steatosis is an additional independent risk factor. We analyzed the Scientific Registry of Transplant Recipients for all adult liver transplants performed from October 1, 2003, through February 6, 2008, with grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
318
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(338 citation statements)
references
References 46 publications
13
318
0
7
Order By: Relevance
“…It may progress towards fibrosis, cirrhosis, and hepatocellular carcinoma [3], it reduces the likelihood of sustained virological response in HCV patients [4] and, in patients undergoing liver resection, it independently increases the risk of postoperative complications and death [5]. In the setting of liver transplantation, the presence of macrovesicular steatosis in the graft increases the 1-year risk of graft failure [6]. Finally, steatosis is the primary lesion in non-alcoholic fatty liver disease (NAFLD), the main cause of CLD in western countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…It may progress towards fibrosis, cirrhosis, and hepatocellular carcinoma [3], it reduces the likelihood of sustained virological response in HCV patients [4] and, in patients undergoing liver resection, it independently increases the risk of postoperative complications and death [5]. In the setting of liver transplantation, the presence of macrovesicular steatosis in the graft increases the 1-year risk of graft failure [6]. Finally, steatosis is the primary lesion in non-alcoholic fatty liver disease (NAFLD), the main cause of CLD in western countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a higher prevalence of nonalcoholic fatty liver disease among men, and patients with obesity, type 2 diabetes, and hyperlipidemia (40). A recent study showed that the presence of more than 30% of macrovesicular steatosis was an independent risk factor for impaired one-year graft survival (41). Therefore detection of significant fatty liver is a critical component of potential living liver donor evaluation.…”
Section: Liver Parenchyma Imagingmentioning
confidence: 99%
“…Se puede utilizar de una manera similar a la de un hígado de un donante >70 años de edad, es decir cuando no exista ningún otro factor de riesgo asociado (10).…”
Section: Donación Después De La Muerteunclassified